2022
DOI: 10.1002/ijgo.14420
|View full text |Cite
|
Sign up to set email alerts
|

How does the ERAS protocol work in patients who underwent cesarean section? (HERMES study)

Abstract: The enhanced recovery after surgery (ERAS) protocol is an evidence-based, multidisciplinary practice that involves preoperative, perioperative, and postoperative interventions, which are aimed at accelerating functional recovery and improving postoperative outcomes. 1 The ERAS protocol aims to minimize complications associated with surgery and shorten the recovery period to an optimum level.A shorter preoperative fasting period, effective pain control, rapid mobilization, and early postoperative feeding are en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Finally, this study showed that PCIA combined with UGTAPB improved postoperative analgesic efficacy and patient satisfaction, and decreased incidence of side effects and opioid consumption. However, this study did not evaluate other important outcome variables of the ERAC, such as the length of hospital stay, time to mobilization, time to urinary catheter removal, the occurrence of postoperative complications, readmission rates, and cost savings [ 6 , 7 ]. Because of this design limitation, an important issue that this study cannot answer is whether improved postoperative pain control and decreased incidence of side effects by PCIA combined with UGTAPB can be translated into the early postoperative benefits of patients undergoing cesarean delivery.…”
mentioning
confidence: 99%
“…Finally, this study showed that PCIA combined with UGTAPB improved postoperative analgesic efficacy and patient satisfaction, and decreased incidence of side effects and opioid consumption. However, this study did not evaluate other important outcome variables of the ERAC, such as the length of hospital stay, time to mobilization, time to urinary catheter removal, the occurrence of postoperative complications, readmission rates, and cost savings [ 6 , 7 ]. Because of this design limitation, an important issue that this study cannot answer is whether improved postoperative pain control and decreased incidence of side effects by PCIA combined with UGTAPB can be translated into the early postoperative benefits of patients undergoing cesarean delivery.…”
mentioning
confidence: 99%